(untitled) (KYAMC Journal, 2025)
Background: Arteriovenous fistula creation is essential for hemodialysis in patients with end-stage renal disease. The choice between local anesthesia and brachial plexus block can impact clinical outcomes. Objective: To compare effectiveness, safety, and patient outcomes associated with local anesthesia (Group A) and brachial plexus block (Group B) in Arteriovenous fistula creation. Materials and Methods: A Cross-sectional study was conducted between September 2022 and June 2023 at the Department of Cardiac Anesthesia & CICU, Khwaja Yunus Ali Medical College & Hospital, Sirajganj. A total of 124 patients were equally divided into two groups: Group A (local anesthesia, n=62) and Group B (brachial plexus block, n=62). Pain levels (measured using a visual analog scale), surgical success rates, postoperative recovery times, and complications were analyzed. Statistical significance was determined using a p-value <0.05. Result: Pain control was significantly better in Group B (mean pain score of 2.1 ± 0.5) compared to Group A (mean pain score of 4.5 ± 1.0) (p < 0.001). The surgical success rate was 95% in Group B and 90% in Group A (p = 0.33). Postoperative recovery times were faster in Group B, with 75% discharged within 24 hours, compared to 55% in Group A (p = 0.03). Group B also had fewer complications, with a hematoma rate of 3%, compared to 10% in Group A (p = 0.04). Conclusion: Brachial plexus block provides significantly better pain relief, faster recovery, and fewer complications compared to local anesthesia in Arteriovenous fistula creation. The results suggest BPB as the superior anesthetic method. KYAMC Journal Vol. 15, No. 04, January 2025: 156-162